Cortico-basal ganglia networks subserving goal-directed behavior mediated by conditional visuo-goal association - Hoshi, Eiji (Frontiers in Neural Circuits, 2013)
Action is often executed according to information provided by a visual signal. As this type of behavior integrates two distinct neural representations, perception and action, it has been thought that identification of the neural mechanisms underlying this process will yield deeper insights into the principles underpinning goal-directed behavior. Based on a framework derived from conditional visuomotor association, prior studies have identified neural mechanisms in the dorsal premotor cortex, dorsolateral and ventrolateral prefrontal cortex, and basal ganglia. However, applications resting solely on this conceptualization encounter problems related to generalization and flexibility, essential processes in executive function, because the association mode involves a direct one-to-one mapping of each visual signal onto a particular action. To overcome this problem, we extend this conceptualization and postulate a more general framework, conditional visuo-goal association. According to this new framework, the visual signal identifies an abstract behavioral goal, and an action is subsequently selected and executed to meet this goal. Neuronal activity recorded from the four key areas of the brains of monkeys performing a task involving conditional visuo-goal association revealed three major mechanisms underlying this process. First, visual object signals are represented primarily in the ventrolateral prefrontal cortex and basal ganglia. Second, all four areas are involved in initially determining the goals based on the visual signals, with the dorsal premotor cortex and dorsolateral prefrontal cortex playing major roles in maintaining the salience of the goals. Third, the cortical areas play major roles in specifying action, whereas the role of the basal ganglia in this process is restrictive. These new lines of evidence reveal that the four areas involved in conditional visuomotor association contribute to conditional visuo-goal association in an area-dependent manner.